Challenges for concrete in tall buildings. (5th November 2014) - Clark, Gordon
Abstract Tall buildings present unique challenges in terms of both design and construction. The definition of tall is always a matter for debate and actually is related to the proportions of the building, although the actual physical height does also result in other influences such as extreme lateral loading. Concrete features prominently in providing the structural material for most cores and framing options, thus ensuring stability of the structure. The core of a tall building is important structurally as well as for forming the spine for vertical transportation and services. There can be a wide choice of size and shape, which is dictated in part by the geometry of the building and the site. This paper focuses on some of the issues for concrete, which is a key material in tall building construction, and is based on some of the work of an fib task group that has been formed to bring together important guidance based on experience of design and construction.